Transformasi peran media sosial sebagai inovasi pembelajaran PAI dalam penguatan minat belajar mahasiswa STITMA Yogyakarta - Muhammad Alwi Alfarezi; Ryki Supratama (Jurnal Ar-Ruhul Ilmi: Jurnal Pendidikan dan Pemikiran Islam, 2025)
The rapid development of information technology has driven significant changes in Islamic Religious Education (PAI) learning, particularly through the use of social media as a learning innovation aligned with the characteristics of the digital generation. At STITMA Yogyakarta, the use of platforms such as YouTube, Instagram, and TikTok has become an alternative strategy in presenting religious learning that is more interactive, flexible, and contextual to students' lives. This study aims to comprehensively analyze the role of social media in increasing learning interest, active engagement, and internalization of Islamic values ​​in students in the digital era. The research method used is a qualitative descriptive approach with research subjects of PAI lecturers and students of the Islamic Religious Education Study Program. Data collection techniques included in-depth interviews, participant observation, and documentation, which were analyzed using the Miles and Huberman interactive model. The results show that social media can increase learning interactivity, expand access to materials, and encourage student creativity through the production of digital da'wah content. However, challenges arise in the form of limited digital literacy, the risk of interference, and issues of ethics and the validity of religious sources. This study concludes that social media plays an important role as an innovation in PAI learning that strengthens motivation and learning quality, provided it is supported by educators' digital competence, ethical guidelines, and integration aligned with the curriculum